A review of the spider genus Hygropoda in Thailand (Araneae, Pisauridae) - Dankittipakul P. (2014)
Three species belonging to the spider genus Hygropoda Thorell are recorded from Thailand. All of them have previously been reported from Yunnan Province, southern China. The males of H. argentata Zhang, Zhu & Song, 2004 and Hygropoda yunnan Zhang, Zhu & Song, 2004 are described and illustrated here for the first time from specimens collected in northern Thailand. The female of H. campanulata Zhang, Zhu & Song, 2004 is redescribed and illustrated from a specimen collected in western Thailand.